Girl Who Kicked the Hornet's Nest - Larsson, Stieg; Keeland, Reg, 1943- (New York : Alfred A. Knopf, 2009)
If and when Lisbeth Salander recovers, she'll be taken back to Stockholm to stand trial for three murders. With the help of her friend, journalist Mikael Blomkvist, she will not only have to prove her innocence, but also identify and denounce those in authority who have allowed the vulnerable, like herself, to suffer abuse and violence. And, on her own, she will plot revenge--against the man who tried to kill her, and the corrupt government institutions that very nearly destroyed her life.
Originally published in Sweden as Luftslottet som sprangdes by Norstedts, Stockholm, in 2007.
Sequel to: The girl who played with fire.
Keywords: Political corruption -- Sweden; Revenge; Suspense fiction